2015
DOI: 10.1093/jee/tov341
|View full text |Cite
|
Sign up to set email alerts
|

Response of Soybean Genotypes Challenged by a Stink Bug Complex (Hemiptera: Pentatomidae)

Abstract: Pentatomids (stink bugs) are major pests of soybean, Glycine max (L.) Merril. These pests reach high levels of infestation, cause severe damage to seeds by feeding, are linked to leaf retention, and are difficult to control. Host plant resistance is considered to be a valuable tool in integrated pest management and can assist in reducing the damage caused by stink bugs. This research evaluated the resistance of soybean genotypes in Brazil to the stink bug complex, the Neotropical brown stink bug, Euschistus he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 56 publications
(47 reference statements)
1
21
0
6
Order By: Relevance
“…Finally, agronomical performance impacts its response to stink bug (Nezara viridula) attacks. Some authors also reported differences in the response of soybean genotypes to stink bug (da Graça et al, 2016;Nomayanja, Tukamuhubwa, & Kyamanywa, 2000;Souza et al, 2016). The different response may be due to different content of soluble leaf phenolics (Zavala, Mazza, Dillon, Chludil, & Ballaré, 2015), the developmental stage of the plant (Kamminga, Koppel, Herbert Jr., & Kuhar, 2012) and developmental stage of the stink bug (Molina & Trumper, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, agronomical performance impacts its response to stink bug (Nezara viridula) attacks. Some authors also reported differences in the response of soybean genotypes to stink bug (da Graça et al, 2016;Nomayanja, Tukamuhubwa, & Kyamanywa, 2000;Souza et al, 2016). The different response may be due to different content of soluble leaf phenolics (Zavala, Mazza, Dillon, Chludil, & Ballaré, 2015), the developmental stage of the plant (Kamminga, Koppel, Herbert Jr., & Kuhar, 2012) and developmental stage of the stink bug (Molina & Trumper, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to these characteristics, it shows low foliar retention, low presence of spots in seeds even during high infestation of stink bugs, and large yield of seeds. These traits make it a potential source of resistant characteristics against damage caused by insects (Pinheiro et al 2005, Souza et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the potential injuries provoked by E. heros, its distribution and predominance over other species of stink bugs, and reported resistance of soybean genotypes against the stink bug complex (Souza et al 2012(Souza et al , 2015Silva et al 2013Silva et al , 2014, studies evaluating the resistance of soybean genotypes against E. heros are crucial. In this work, we assessed several biological parameters of E. heros on 17 soybean genotypes of different maturity groups, with the aim of identifying potential antibiosis.…”
mentioning
confidence: 99%
“…This study corroborates the second possibility because there is a correlation between the weight of 100 seeds and protein content (Table 1). The resistance of soybean genotypes varies from the least infested, low yield reduction, low levels of damage in seeds and low levels of leaf retention (Souza et al 2016). There are some gene families associated with nucleotidebinding and receptor-like proteins serving in the plant's biotic resistance (McHale et al 2012).…”
Section: Relationship Between Protein Content and Agronomical Charactersmentioning
confidence: 99%
“…Soybean plant has tolerance mechanism to limit reduction in seed yield (Souza et al 2016). The ratio of unfilled pods to total pods describes the tolerance of a genotype to N. viridula infestation.…”
Section: Relationship Between Protein Content and Agronomical Charactersmentioning
confidence: 99%